2014
DOI: 10.1586/17434440.2014.946695
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented hip joint replacements, femoral replacements and femoral fracture stabilizers

Abstract: This paper reviews instrumented hip joint replacements, instrumented femoral replacements and instrumented femoral fracture stabilizers. Examination of the evolution of such implants was carried out, including the detailed analysis of 16 architectures, designed by 8 research teams and implanted in 32 patients. Their power supply, measurement, communication, processing and actuation systems were reviewed, as were the tests carried out to evaluate their performance and safety. These instrumented implants were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 99 publications
0
33
0
Order By: Relevance
“…Ledet et al [74] conducted an overview on sensor technology for instrumented orthopedic implants focused on physical parameters that do not provide an effective indication of the bone-implant integration state (characteristics, strength, stiffness, etc). Soares dos Santos et al [21,75] focused their analyses on all bioelectronic systems (actuation, monitoring, communication, and self-powering) incorporated into instrumented bone implants experimentally validated in vivo, which also confined the measurement technologies to force, moment, and temperature sensors. Karipott et al [76] also presented an enumeration of some technologies for biomechanical loading and biochemistry monitoring, but only three studies on implant failure detection were briefly reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ledet et al [74] conducted an overview on sensor technology for instrumented orthopedic implants focused on physical parameters that do not provide an effective indication of the bone-implant integration state (characteristics, strength, stiffness, etc). Soares dos Santos et al [21,75] focused their analyses on all bioelectronic systems (actuation, monitoring, communication, and self-powering) incorporated into instrumented bone implants experimentally validated in vivo, which also confined the measurement technologies to force, moment, and temperature sensors. Karipott et al [76] also presented an enumeration of some technologies for biomechanical loading and biochemistry monitoring, but only three studies on implant failure detection were briefly reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the uncemented fixation is more prone to induce bone loss due to stress shielding, a mechanical phenomenon resulting from different mechanical stimuli patterns delivered to the periprosthetic bone stock occurring after implant insertion [18,20]. Revision rates related to stress shielding-induced bone loss can exceed 50%, with incidences confirming implant loosening among the most common causes indicating bone replacement [1,21]. An accurate control of the factors modulating the bone-implant integration process is, then, mandatory to establish an asymptomatic and stable long-term fixation [20,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations